The Effect Of Content Marketing In Enhancing Broad Awareness-An Analytical Study Of The Opinions Of A Sample Of Managers Two Employees Xerox Media Advertising And Marketing Company In Governorate Holy Karbala - Assistant Lecturer Kamal Muhammed Yaqoob (Peerian Journals Publishing, 2024)
The purpose of this research is to clarify the impact of content marketing with its dimensions including (relevance, credibility, value, emotion, attractiveness) on enhancing broad advocacy with customers (Xerox Media Advertising and Marketing Company in Holy Karbala). To achieve this goal or purpose, this research sought to follow the descriptive and analytical approach, as the questionnaire form was relied upon to obtain data and referendums, and the sampling method was used with all employees of the company. Xerox Media for advertising and marketing, the researcher also distributed (111) questionnaire forms, and the valid forms for treatment were (104) forms and were analyzed statistically. The research found that the level of understanding and awareness of the company’s employees was very high for marketing content to appear better than broad recommendation. The results also show that there is a positive and statistically significant relationship between content marketing and broad recommendation from the employees’ point of view. This research recommended the need for Xerox Media Advertising and Marketing to pay attention to content marketing because of its role. Relevance and influence on the wide recommendation of employees and customers. The research also recommended providing clear and accurate information content regarding the products and services it provides.Company Xerox Media For advertising And marketing In order to increase customers’ confidence in the content provided to them
Keywords: content marketing; broad advertising; Xerox Media Advertising